Encephalic nocardiosis after mild COVID-19: A case report - Bouhamdani, Nadia; Comeau, Dominique; Bourque, Christine; Saulnier, Nancy (Frontiers in Neurology, 2023)
The COVID-19 pandemic and the associated post-acute sequelae of COVID-19 (PASC) have led to the identification of a complex disease phenotype that is associated with important changes in the immune system. Herein, we describe a unique case of Nocardia farcinica cerebral abscess in an individual with sudden immunodeficiency several months after mild COVID-19. Intravenous Bactrim and Imipenem were prescribed for 6 weeks. After this, a 12-month course of Bactrim and Clavulin was prescribed to be taken orally, given the N. farcinica infection at the level of the central nervous system. This case report highlights the need for future research into the pathophysiology of COVID-19 and PASC immune dysregulation in convalescent individuals. It also draws attention to the need for timely consideration of opportunistic infections in patients with a history of COVID-19.